Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe 2: Profil HbA1c dan Lipid di Klinik Aulia Jombang 2020 - Ronald Pratama A.; Cahya Yudha Laksmana Putra; Retno Budiarti; Oki Nugraha Putra; Angelica Kresnamurti; Sulistiawati Sulistiawati (Journal of Pharmaceutical and Sciences, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by high blood sugar levels due to insulin secretion or work defects. Poor treatment adherence leads to uncontrolled glycemic levels and complications. Therefore, ensuring patient adherence to therapy and reducing HbA1c and lipid profiles is essential. This research employs an observational, cross-sectional design, using non-probability purposive sampling to select 55 respondents via the Slovin formula. The study examines medication adherence as the independent variable, Hba1c levels, and lipid profile as the dependent variables. Data analysis involves SPSS, utilizing univariate and bivariate methods for ordinal and nominal scales. MMAS-8 questionnaire assesses the knowledge, while data comes from questionnaires and medical records of type 2 DM patients at Aulia Jombang Clinic. Study findings showed notable adherence to treatment, with 38 respondents (60.9%) complying and 17 (30.1%) not. Chi-square tests yielded significance, p values: HbA1c 0.012, LDL 0.035, total cholesterol 0.008, triacylglycerides 0.011, and HDL 0.002, based on MMAS-8 questionnaire data. In conclusion, the results indicate statistical significance (p-value < 0,05), so there is a positive correlation coefficient, indicating that higher levels of treatment adherence are associated with more optimal HbA1c control and lipid profiles.